Characteristics of recreational substance consumption in night clubs in the Aburrá Valley - Gloria I. Martínez D; Lina M. Martínez S; María A. Rodríguez G; Cristian C. Benítez R; Catalina Franco R (Universidad de Antioquia, 2011)
Objective: to explore the demographic characteristics and the features of "recreational substance" consumption in people attending night clubs located in some of the municipalities of the Aburrá Valley. Methodology: we designed a crosssectional study; the population was made-up of adult males and females that attend night clubs in the Aburrá Valley. The sonar 98 modified survey was adapted by the researchers for use in this study. Results: we studied 17 night clubs. A total of 789 people participated, 57.7% of them were female, and the mean age was 23 years; 61.0% of the subjects were students. Most of the surveyed population had consumed at some point of their lives: alcohol (95%), cigarette (46.0%), cannabis (25.0%), amylnitrite or "Popper" 10.0%, "designed drugs" such as amphetamines and methamphetamines (9.0%) and sedatives and hypnotics (10.0%). Consumption first started early in life with the so-called social drugs: alcohol (at 14) and cigarette smoking (at 15). Discussion: unlike results from other worldwide studies, our exploratory survey showed that recreational drug consumption starts with socially accepted substances such as alcohol and cigarette, whereas designed drugs and other drugs have a more restricted use, and their consumption starts at older ages.